Children and social exclusion : morality, prejudice, and group identity - Killen, Melanie; Rutland, Adam. (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2011)
"Children and Social Exclusion: Morality, Prejudice, and Group Identity explores the origins of prejudice and the emergence of morality to explain why children include some and exclude others. Formulates an original theory about children's experiences with exclusion and how they understand the world of discrimination based on group membership Brings together Social Domain Theory and Social Identity Theory to explain how children view exclusion that often results in prejudice, and inclusion that reflects social justice and morality Presents new research data consisting of in-depth interviews from childhood to late adolescence, observational findings with peer groups, and experimental paradigms that test how children understand group dynamics and social norms, and show either group bias or morality Illustrates data with direct quotes from children along with diagrams depicting their social understanding Presents new insights about the origins of prejudice and group bias, as well as morality and fairness, drawn from extensive original data"--Provided by publisher.
"Social inclusion and exclusion are pervasive aspects of social life. Understanding when exclusion is legitimate or wrong reflects an understanding of morality. While there are times when exclusion is legitimate and fosters group functioning, there are also times when it reflects prejudicial biases and stereotypic expectations. How children weigh fairness and stereotypic expectations when making exclusion decisions is determined by their understanding of group norms, social identity, and friendships with children from other backgrounds. In our contemporary global society, few topics are as timely or pressing as exclusion. Children and Social Exclusion: Morality, Prejudice, and Group Identity delves deeply into the origins of prejudice and the emergence of morality to explain why children include some and exclude others and sheds light on the origins of stereotyping, prejudice, and social justice. By tackling these important issues from a global perspective, Children and Social Exclusion: Morality, Prejudice, and Group Identity illustrates how the concept of exclusion might be better understood in multiple cultures and reveals its implications in regions of conflict in the world"--Provided by publisher.
Machine generated contents note: Dedication. -- Preface. -- Chapter 1: Introduction: Exclusion and Inclusion in Children's Lives. -- Chapter 2: Emergence of Morality and Inclusion. -- Chapter 3: Emergence of Categorization and Prejudice. -- Chapter 4: Development of Group Identity and Prejudice. -- Chapter 5: What we know about Peer Relations, Group Identity, and Exclusion. -- Chapter 6: Intragroup and Intergroup Exclusion: An In-depth Study. -- Chapter 7: Peer Exclusion and Group Identity Around the World: The Role of Culture. -- Chapter 8: Interventions for Promoting Morality and Positive Intergroup Attitudes. -- Chapter 9: Integration of Morality, Prejudice, and Group Identity: A New Perspective. -- References. -- List of Figures and Tables.
Includes bibliographical references and index.
Keywords: Social integration; Children; Group identity; Identity (Psychology); Prejudices; Children; Group identity; Identity (Psychology); Prejudices; Social integration; Electronic books